The third dimension (3D) in the presentation of noise distribution on building facades - as shown by the example of a fragment of a residential estate in Poznań - Kubiak, Jarosław (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2015)
The work attempts to visualise the distribution of the acoustic wave in an urban area using a 3D model. The primary objective was to present the level of noise on facades of buildings. The studied area was a fragment of a residential estate in Poznań. The geometry of the topographical objects was obtained from the GBDOT. A three dimensional model of the building development of the area was made using the Google SketchUp program. The input data for the interpolation of isophones were taken from direct field measurements. Attempts were made to obtain measurement data from road sources. The obtained values were averaged for 16 hours of the daytime. Ranges of the individual noise levels determined by the isophones were marked in colours. The applied software enables displaying the noise distribution on building facades, viewing it at various angles and making animations. The work presents the use of a 3D model for an urban area. The model is expected to improve the information database regarding noise hazards in a built-up area.
Keywords: noise mapping; 3D model; environmental information; sound visualization; public participation; thematic cartography